Kaji Eksperimental Perpindahan Panas Peleburan Parafin Sebagai Material Penyimpan Panas pada Alat Penukar Kalor Bersirip - - Zulkifli; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
In this research, experimental study is conducted related to the latent heat transfer and thermal energy storage using finned tubes. An experimental unit consisted of data acquisition, the heat exchanger shell and tube were used to improve heat transfer. The fluid heat pipe was designed in longitudinal fin and radial fin. Paraffin wax was used as a thermal storage medium. The characteristics of heat transfer from fluid to paraffin wax is investigated in different heat flux conditions. The experimental results show that the heat transfer characteristics show similarities to the heat exchanger tubes. In the preheating process, it is dominated by conduction, but at the melting temperature of the heat transfer, it is dominated by convection. The use of longitudinal finned pipe has been able to increase the heat transfer rate.